Progress in transition metal chalcogenides-based counter electrode materials for dye-sensitized solar cells. (15th March 2023) - Sheela, Sowbakkiyavathi Elindjeane; Sekar, Ramkumar; Maurya, Dheeraj Kumar; Paulraj, Manidurai; Angaiah, Subramania
Abstract: Dye-sensitized solar cell (DSSC) is considered as an excellent indoor photovoltaic (PV) technology because it shows better performance even in scattered indoor light, low cost, high flexibility, semi-transparency in nature and availability of variety of colors. Counter Electrode (CE) is one of a crucial component in DSSC as it collects electrons from the external circuit and also act as a catalyzer towards iodide/triiodide (I − /I3 − ) redox couple in the electrolyte. Platinum (Pt) noble metal is commonly used as a CE material for designing DSSC. But, due to high cost and corrosion activity towards the I − /I3 − reduction process, Pt lost its application. Hence, in order to develop a Pt-free CE, several new materials have been explored to fabricate highly efficient DSSC. In this review, the recent progress of binary and ternary transition metal chalcogenides (TMC) and their composites as an effective CE to replace expensive Pt metal CE in DSSC are discussed.